Recycling Education and Compost Waste Processing to Improve Environmental Cleanliness and Health at an Orphanage for Children - Annisa Syahliantina; Rudy Effendi Listyanto; Fibi Eko Putra; Ghina Farhah Azizah; Gustomi Nugroho (DPPM Universitas Pelita Bangsa, 2026)
Barokah Amanah Mustaqbal Orphanage in Karawang faces challenges in household waste management, including the absence of waste segregation practices, the lack of organic waste processing, and limited awareness among residents regarding the importance of maintaining environmental cleanliness. These conditions have the potential to cause environmental pollution and negatively affect the health and comfort of the orphanage residents. This Community Service Program aimed to improve the knowledge and skills of the orphanage residents and administrators in waste management through environmental education and the application of appropriate technology. The program was implemented through preliminary observations, educational sessions on waste management, training on waste segregation, hands-on composting practice using a simple composter, and continuous mentoring to ensure program sustainability. The results showed that participants gained a better understanding of proper waste management practices, waste segregation facilities were established, organic waste processing using a simple composter was successfully implemented, and an environmental awareness group was formed to support the continuity of the program. The application of a simple composter proved to be a practical and affordable solution for managing organic waste in accordance with the needs and conditions of the orphanage, while educational and mentoring activities encouraged the development of environmentally responsible behavior. Overall, the program provided an effective solution to waste management problems and contributed to creating a cleaner, healthier, more comfortable, and sustainable living environment within the orphanage.